RESEARCH IN LANDSLIDE AND FLOOD STRENGTHENS MALAYSIA - JAPAN COLLABORATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PUTRAJAYA, 17 March 2016 – The success of the project entitled ‘Research and Development for Reducing GeoHazard Damage in Malaysia Caused by Landslide and Flood’ has become among the first to be completed under the smart partnership initiative of 'Science and Technology Research Partnership for Sustainable Development' (SATREPS) in Malaysia, involving the cooperation of various partners from Japan.